2017
DOI: 10.1186/s12966-017-0472-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of universal interventions on social inequalities in physical activity among older adults: an equity-focused systematic review

Abstract: BackgroundPhysical activity is one of the most important contributors to healthy aging. Public health strategies aiming to promote physical activity among older adults are increasingly being implemented. However, little is known about their impact on social inequalities. Purpose of the study was to analyze whether and how studies of interventions consider effects on social inequalities in physical activity among older adults.MethodsNine electronic databases were searched to identify quantitative studies evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 60 publications
2
44
2
2
Order By: Relevance
“…However, evidence suggests that PA interventions are less effective in low-income groups, potentially widening rather than reducing inequalities [49]. Worryingly, a recent systematic review identified that there is insufficient evidence to allow for firm conclusions to be made regarding the impact of PA interventions on inequalities [53]. According to the WHO, effective national action to reduce disparities in PA requires a strategic combination of population-based policy actions aimed at tackling the "upstream" determinants that shape the equity of opportunities for participation (such as encouraging nonmotorised modes of travel through improved provision of cycling and walking infrastructure, improved road safety, and creating more opportunities for PA in public open spaces and local community settings [54]) and those policy actions that are focused on "downstream" individually-focused (educational and informational) interventions, implemented in ways consistent with the principle of proportional universality (i.e.…”
Section: Implications For Policymentioning
confidence: 99%
“…However, evidence suggests that PA interventions are less effective in low-income groups, potentially widening rather than reducing inequalities [49]. Worryingly, a recent systematic review identified that there is insufficient evidence to allow for firm conclusions to be made regarding the impact of PA interventions on inequalities [53]. According to the WHO, effective national action to reduce disparities in PA requires a strategic combination of population-based policy actions aimed at tackling the "upstream" determinants that shape the equity of opportunities for participation (such as encouraging nonmotorised modes of travel through improved provision of cycling and walking infrastructure, improved road safety, and creating more opportunities for PA in public open spaces and local community settings [54]) and those policy actions that are focused on "downstream" individually-focused (educational and informational) interventions, implemented in ways consistent with the principle of proportional universality (i.e.…”
Section: Implications For Policymentioning
confidence: 99%
“…Where an aggregated estimation of effect is required, we advocate this approach. Where individual studies may be insufficiently powered to undertake subgroup analyses, consistent reporting of intervention effects in subgroups across studies will allow subsequent pooling to establish differential intervention characteristics among specific subpopulations [112]. We argue that there is a role for more contextual, in-depth evaluation however, and an expanded evidence-base as presented here [21].…”
Section: Evidence Of Effectivenessmentioning
confidence: 86%
“…While we did not exclude by design, the lack of RCTs was notable, given recent recommendations for such evaluations [24,112]. Where an aggregated estimation of effect is required, we advocate this approach.…”
Section: Evidence Of Effectivenessmentioning
confidence: 99%
“…However, evidence suggests that PA interventions are less effective in low-income groups, potentially widening rather than reducing inequalities [49]. Worryingly, a recent systematic review identified that there is insufficient evidence to allow for firm conclusions to be made regarding the impact of PA interventions on inequalities [53].…”
Section: Implications For Policymentioning
confidence: 99%